2020
DOI: 10.1183/16000617.0240-2020
|View full text |Cite
|
Sign up to set email alerts
|

Targeting coagulation activation in severe COVID-19 pneumonia: lessons from bacterial pneumonia and sepsis

Abstract: Novel coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2), has rapidly spread throughout the world, resulting in a pandemic with high mortality. There are no effective treatments for the management of severe COVID-19 and current therapeutic trials are focused on antiviral therapy and attenuation of hyper-inflammation with anti-cytokine therapy. Severe COVID-19 pneumonia shares some pathological similarities with severe bacterial pneumonia and sepsis. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 115 publications
1
16
0
1
Order By: Relevance
“…Skendros et al, recently showed that complement and tissue factor were identified as a key driver in COVID-19 severity: (47). Tissue factor (TF) is initiating downstream cascades involving factor X (48). Here, we confirm that SARS-CoV-2-infected hamster exhibit distinct factor X as well as complement C3c protein level in inflamed lung biopsies (Supplementary Figures 1-4).…”
Section: Endothelialitis and Vasculitis In Lungs Of Golden Syrian Hamster (Hamster) At 3 And 6 Days Post Infection (Dpi)supporting
confidence: 77%
“…Skendros et al, recently showed that complement and tissue factor were identified as a key driver in COVID-19 severity: (47). Tissue factor (TF) is initiating downstream cascades involving factor X (48). Here, we confirm that SARS-CoV-2-infected hamster exhibit distinct factor X as well as complement C3c protein level in inflamed lung biopsies (Supplementary Figures 1-4).…”
Section: Endothelialitis and Vasculitis In Lungs Of Golden Syrian Hamster (Hamster) At 3 And 6 Days Post Infection (Dpi)supporting
confidence: 77%
“…Several studies demonstrated that dysregulation of procoagulant and fibrinolytic pathways may uniquely contribute to the pathophysiology of sepsis. However, this issue should be further investigated to obtain more details ( Bouck et al., 2020 ; Colantuoni et al., 2020 ; Jose et al., 2020 ; Kang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, vitamin C deficiency appears to be common among COVID-19 patients ( 110 , 111 ). COVID-19 is also associated with the formation of microthrombi and coagulopathy ( 112 ), which contribute to its characteristic lung pathology ( 113 ), but these symptoms can be ameliorated by early infusions of vitamin C to inhibit endothelial surface P-selectin expression and platelet-endothelial cell adhesion ( 114 ). Intravenous vitamin C also reduced D-dimer levels in a case study of 17 COVID-19 patients ( 115 ).…”
Section: Vitamin Cmentioning
confidence: 99%